Sustainability of urban aquaponics farms: An emergy point of view - David, Luiz H. [UNESP] (2022)
Aquaponics is a food production system that aims higher sustainability by integrating advantages gained from aquaculture and hydroponic production. Aquaponics aims to mimic the biological process that happens in the natural environment in a controlled production system. As it can be applied to small scales, aquaponics is considered an important alternative for urban regions, which have low availability of agricultural land and water resources. Furthermore, the advantage is that it is located close to final consumers. Aquaponics has been labeled as an environmentally friendly food production system, but its demand for energy and materials cast doubt on its sustainability. A systemic understanding of aquaponics production systems is needed to determine the magnitude and balance between its potentialities and constraints, in which emergy synthesis appears as a powerful tool for this purpose. This study applies emergy synthesis to assess the sustainability of two different (scale and marketable products) urban aquaponics farms in Brazil, but differently from other emergy studies, ecosystem services and disservices are included in the analysis as an attempt to represent the system performance holistically. Results show that the type of materials used in aquaponics infrastructures has the highest influence on total emergy demand. Surprisingly, electricity and fish feed showed a low influence on the total emergy, reinforcing the idea that aquaponics systems have a more efficiency feeding management than traditional aquaculture systems. Besides producing vegetables and fish, the inclusion of ecosystem services highlights the importance of aquaponics for educational and tourism purposes. Finally, the obtained indicators from modeling scenarios revealed that replacing the water source and some materials deserves priority attention to increase the sustainability of urban aquaponics farms.